PERAN ORGANISASI KEAGAMAAN DALAM MENDORONG KESEJAHTERAAN SOSIAL DI MASYARAKAT (STUDI KASUS ORGANISASI HIMMAH MEDAN) - Ahmad Sujai Tanjung; Fitri Nadilla Marpaung; Chodijjah Nur Syahfitri; Luthfi Azhari; Dhifa Yunisa Meida Hasibuan; Cipta Novian; Sri Purwasih Simamora; Safitriani; Reh Ulina; Rasdalifah; Rina Riski Nasution; Riyan Syah Afendi (Kampus Akademik Publiser, 2025)
This study aims to examine the role of the religious organization HIMMAH in improving social welfare in Medan City. The methodology used is qualitative with field ethnography techniques, involving observation and semi-structured interviews. The results of the study indicate that HIMMAH has succeeded in improving access and quality of education, health, and the economy through programs designed in a participatory and collaborative manner. Key success factors include active community involvement, operational transparency, and strategic collaboration with the government and donor agencies. These findings provide important insights for similar organizations to improve the effectiveness of their social interventions.